2002
DOI: 10.7589/0090-3558-38.4.851
|View full text |Cite
|
Sign up to set email alerts
|

Normal Conjunctival Flora in the North American Opossum (Didelphis virginiana) and Raccoon (Procyon lotor)

Abstract: We documented the normal conjunctival bacterial flora from 17 opossums (Didelphis virginiana) and 10 raccoons (Procyon lotor) trapped in Manhattan, Kansas (USA) from November 1999 to January 2000. Both raccoons and opossums were free of apparent ocular disease. The inferior conjunctival sacs of each animal were swabbed for aerobic bacterial and Mycoplasma culture and polymerase chain reaction (PCR) for Mycoplasma and Chlamydia detection. All conjunctival samples were positive for one or more species of aerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 15 publications
5
28
0
2
Order By: Relevance
“…Ocular microbiota has been described in many different species of animals . Results of this investigation demonstrate that the microbiota of the eye surface of microbats is composed of a diverse bacterial spectrum.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Ocular microbiota has been described in many different species of animals . Results of this investigation demonstrate that the microbiota of the eye surface of microbats is composed of a diverse bacterial spectrum.…”
Section: Discussionmentioning
confidence: 83%
“…Ocular microbiota has been described in many different species of animals. [8][9][10] Results of this investigation demonstrate that the microbiota of the eye surface of microbats is composed of a diverse bacterial spectrum. No other studies of ocular microbiota of bats could be found; thus, these results could not be directly compared with other such studies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…One study detected Mycoplasma sp. in conjunctival swabs of healthy, freeranging raccoons, so it is unknown if disease is the result of opportunistic infection of a commensal organism (Pinard et al, 2002).…”
Section: Bacteriamentioning
confidence: 99%
“…However, mycoplasma (including hemoplasma) infections of raccoons (Procyon lotor) are poorly studied (26). In 1971, Haemobartonella procyoni was described in raccoons from Maryland, USA (27).…”
mentioning
confidence: 99%